Evolutionarily conserved and species-specific glycoproteins in the N-glycoproteomes of diverse insect species. (September 2018) - Scheys, Freja; Van Damme, Els J.M.; De Schutter, Kristof; Staes, An; Gevaert, Kris; Smagghe, Guy
Abstract: N-glycosylation is one of the most abundant and conserved protein modifications in eukaryotes. The attachment of N-glycans to proteins can modulate their properties and influences numerous important biological processes, such as protein folding and cellular attachment. Recently, it has been shown that protein N-glycosylation plays a vital role in insect development and survival, which makes the glycans an interesting target for pest control. Despite the importance of protein N-glycosylation in insects, knowledge about insect N-glycoproteomes is scarce. To fill this gap, the N-glycosites were identified in proteins from three major pest insects, spanning different insect orders and diverging in post-embryonic development, feeding mechanism and evolutionary ancestry: Drosophila melanogaster (Diptera), Tribolium castaneum (Coleoptera) and Acyrthosiphon pisum (Hemiptera). The N-glyco-FASP method for isolation of N-glycopeptides was optimized to study the insect N-glycosites and allowed the identification of 889 N-glycosylation sites in T. castaneum, 941 in D. melanogaster and 1338 in A. pisum . Although a large set of the corresponding glycoproteins is shared among the three insects, species- and order-specific glycoproteins were also identified. The functionality of the insect glycoproteins together with the conservation of the N-glycosites throughout evolution is discussed. This information can help in the elaboration of novel pest insect control strategies based on interference in insect glycosylation. Graphical abstract: Image 1 Highlights: Optimization of the N-glyco-FASP isolation method for insect samples. Identification of the N-glycoproteome of insects spanning diverse insect orders. About 60% of the identified N-glycoproteins are evolutionarily conserved in three species. Species- and order-specific N-glycoproteins were identified in all species under study.